Koeksistensi Spondiloartritis Perifer dan Fokal Segmental Glomerulosklerosis: Sebuah Laporan Kasus Jarang - Zulaifah, Zakiya; Hapsari, Florentina Carolin Puspita; Muzellina, Virly Nanda (UI Scholars Hub, 2026)
Spondyloarthritis is a group of inflammatory rheumatic diseases characterized by shared clinical features, genetic predispositions, and pathogenic mechanisms. Without appropriate management, it carries a risk of various complications. We report the case of a young male patient with a one-year history of nephrotic syndrome prior to admission, presenting with chronic polyarthritis. Initially, systemic lupus erythematosus (SLE) with renal and musculoskeletal involvement was suspected, although SLE is relatively uncommon in young males. However, based on the clinical presentation of arthritis, imaging findings of sacroiliitis, and the absence of diagnostic criteria supporting SLE, the patient was subsequently diagnosed with peripheral spondyloarthritis and nephrotic syndrome secondary to focal segmental glomerulosclerosis (FSGS). Patients with spondyloarthritis have approximately a twofold increased risk of renal complications compared with the general population, with IgA nephropathy being the most common abnormality. Although rare, cases of spondyloarthritis occurring in patients with FSGS have been reported. The relationship between these two conditions remains unclear—whether causal or coincidental—and warrants further investigation. A careful diagnostic approach is essential in patients with chronic polyarthritis, particularly when differential diagnoses do not align with demographic characteristics or clinical presentation. This is crucial to improve diagnostic accuracy, guide appropriate therapy, enable earlier prevention of disease progression, and reduce the risk of complications.